2022
DOI: 10.1038/s41598-022-19400-4
|View full text |Cite
|
Sign up to set email alerts
|

Neovascular age-related macular degeneration without exudative recurrence over 24 months after initial remission

Abstract: We investigated the characteristics of neovascular age-related macular degeneration (AMD), which rarely recurs after initial remission. This study retrospectively analyzed 392 neovascular AMD patients treated with anti-vascular endothelial growth factor (VEGF). All patients received three monthly loading doses of anti-VEGF injections, followed by a pro re nata (as needed) regimen for 24 months. The baseline characteristics associated with the odds of having no recurrence within 24 months were evaluated using m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Several investigators investigated factors predictive of complete remission after the loading injections and reported that smaller lesion size and younger age were associated with complete remission. 10 In this study, protective variants of ARMS2 and younger ages were associated with a 12-month remission. The risk allele of ARMS2 was reportedly associated with larger lesion size.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Several investigators investigated factors predictive of complete remission after the loading injections and reported that smaller lesion size and younger age were associated with complete remission. 10 In this study, protective variants of ARMS2 and younger ages were associated with a 12-month remission. The risk allele of ARMS2 was reportedly associated with larger lesion size.…”
Section: Discussionmentioning
confidence: 52%
“…Several studies have investigated the incidence of a complete remission rate after the initial loading phase of anti-VEGF therapy for exudative AMD. Cho et al 10 Fig. 4.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the cornea, SP has been shown to cause avascular hemangiogenesis and lymphangiogenesis in mice models. Topical application of NK1 antagonist, Lanepitant, was shown to reduce the angiogenesis within the inflamed cornea, and this was also shown to occur with topical Fosaprepitant [173,174]. In a recent paper, ocular mast cells were also shown to cause increased inflammatory angiogenesis or neovascularization due to release of VEGF-A in mouse models of corneal inflammation [175].…”
Section: Therapeutic Applications Of Sp In Cornea Epitheliummentioning
confidence: 98%
“…Fosaprepitant [173,174]. In a recent paper, ocular mast cells were also shown to cause increased inflammatory angiogenesis or neovascularization due to release of VEGF-A in mouse models of corneal inflammation [175].…”
Section: Therapeutic Applications Of Sp In Cornea Epitheliummentioning
confidence: 99%